THE EFFECT OF TRI HITA KARANA CULTURE ON FINANCIAL PERFORMANCE IN VILLAGE CREDIT INSTITUTIONS (LPD) IN BADUNG DISTRICT - Ni Rai Artini (Vidyottama Sanatana: International Journal of Hindu Science and Religious Studies, 2024)
In Bali, the Village Credit Institution (LPD) has emerged as a noteworthy microfinance institution, characterized by its unique ownership structure tied to traditional village institutions. This institution's legitimacy is anchored in Governor of Bali Decree Number 3 of 2017, bolstered by the implementing regulations outlined in Governor of Bali Regulation No. 44 of 2017. The primary objective of this study is to investigate the impact of the Tri Hita Karana culture on the financial performance of Village Credit Institutions (LPDs) in Badung Regency. The Tri Hita Karana culture is assessed using subvariables encompassing Parahyangan, Pawongan, and Palemahan elements. The financial performance of LPDs is gauged using the Return On Asset (ROA) ratio. Data collection was conducted through cross-sectional surveys employing a Likert scale, with the Village Credit Institutions (LPDs) in Badung Regency as the unit of analysis. The study involved 55 respondents, specifically the heads of LPDs, selected using Proportional Random Sampling. Path analysis was employed as the method for hypothesis testing. The findings of this research underscore the positive and statistically significant influence of the Tri Hita Karana culture, encompassing its subvariables of Parahyangan, Pawongan, and Palemahan, on the financial performance of Village Credit Institutions (LPDs) in Badung Regency. As a result, it is strongly recommended that LPD leadership actively promotes and integrates the Tri Hita Karana culture into their operations, serving as a guiding principle for LPD managers. This cultural emphasis is poised to enhance the overall financial performance of LPDs, thus fostering sustainable development and empowerment within the local community.